A five year financial plan for Eurobrass Products Inc - Mendoza, Maribeth B. et. al. 4 0 16; 5 (2016)
EXECUTIVE SUMMARY: Eurobrass Product Incorporated is a manufacturer and distributor of quality drains, ductile iron, cast iron, trench grating, grease traps, manhole cover, basket strainer, planters box, catch basin cover and steel and grease/oil interceptor. The company is also known in the construction industry for its valve box covers which carries the brand name jaman. Since its establishment in 1994, the company is 100% Filipino-owned. Based on the initial prospectus, the company is acquiring relatively significant amount of fixed assets to improve its operations. From 2020 to 2014, Eurobrass Product Inc. percentage of net income to net sales have consistently decreased and only ranged from 1.99% - 1.80% because of high percentage of cost sales ranging from 83% - 88%. Inspite of this, it is evident that the company is expanding its operations with an overall growth of 60% in net sales from 2010 to 2014. At present, Eurobrass Product, Inc. maintains 11 equipment and 22 machineries of various functions and operations administered by 11 skilled workers and engineers. With a prime banking grade and credit rating, they are dedicated in improving their production equipment and facilities to further improve efficiency in creating functional and innovative products. Eurobrass Product Inc. does not have enough cash. For the last 5 years, the company's cash doesn't hit P1,000,000 that is why the company need to resort with creating a contractor to fund their expansion. Also, with the acquisition of large amount of fixed asset in the form of building that is under construction, it would have a negative impact on their return on assets ratio. Lastly, vast majority of the company's assets is financed thru debt resulting to a high debt-to-quality ratio. Upon analysing the company's financial position, the analysts have come up to the recommendation that the company should Refinance through long-term debt while shifting sources of raw materials from foreign suppliers. This alternative course of action will increase the company's available cash by up to 169% and will lessen the company's cost of sales by 10%. After implementing the proposed alternative course of action, and after the projected financial statements have been made, the company's profitability, liquidity and solvency ratios have improved significantly as compared to their 2014 ratios.
Financial Plan: (BSBA major in Finance and Treasury Management)- Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2